A scoping review of perceptions from healthcare professionals on antipsychotic prescribing practices in acute care settings - Natalia Jaworska; Stephana J. Moss; Karla D. Krewulak; Zara Stelfox; Daniel J. Niven; Zahinoor Ismail; Lisa D. Burry; Kirsten M. Fiest (BMC, 2022)
Abstract Background Antipsychotic medications are frequently prescribed in acute care for clinical indications other than primary psychiatric disorders such as delirium. Unfortunately, they are commonly continued at hospital discharge and at follow-ups thereafter. The objective of this scoping review was to characterize antipsychotic medication prescribing practices, to describe healthcare professional perceptions on antipsychotic prescribing and deprescribing practices, and to report on antipsychotic deprescribing strategies within acute care. Methods We searched MEDLINE, EMBASE, PsycINFO, CINAHL, and Web of Science databases from inception date to July 3, 2021 for published primary research studies reporting on antipsychotic medication prescribing and deprescribing practices, and perceptions on those practices within acute care. We included all study designs excluding protocols, editorials, opinion pieces, and systematic or scoping reviews. Two reviewers screened and abstracted data independently and in duplicate. The protocol was registered on Open Science Framework prior to data abstraction (10.17605/OSF.IO/W635Z). Results Of 4528 studies screened, we included 80 studies. Healthcare professionals across all acute care settings (intensive care, inpatient, emergency department) perceived prescribing haloperidol (n = 36/36, 100%) most frequently, while measured prescribing practices reported common quetiapine prescribing (n = 26/36, 76%). Indications for antipsychotic prescribing were delirium (n = 48/69, 70%) and agitation (n = 20/69, 29%). Quetiapine (n = 18/18, 100%) was most frequently prescribed at hospital discharge. Three studies reported in-hospital antipsychotic deprescribing strategies focused on pharmacist-driven deprescribing authority, handoff tools, and educational sessions. Conclusions Perceived antipsychotic prescribing practices differed from measured prescribing practices in acute care settings. Few in-hospital deprescribing strategies were described. Ongoing evaluation of antipsychotic deprescribing strategies are needed to evaluate their efficacy and risk.